Adaptasi Pegadaian (Persero) dalam rangka Meningkatkan Efisiensi dan Efektivitas Pelayanan kepada Masyarakat (Studi Kasus pada Pegadaian Cabang Malang) - Hasan Bisri (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2016)
In implementing development in the economy, the State Owned Enterprises (SOEs) are required to have a commitment to lift the people from the shackles of poverty, therefore, there are three (3) legal form of state enterprises, namely: Corporate Office (PERJAN), Public Company (PERUM) and the Company (PERSEROAN). Since it was first established and provide services, pawnshop has several times changed the status of a legal entity, namely as a State Company (PN) since January 1, 1961, then based PP.No.7 / 1969 to the Corporate office (PERJAN). Furthermore, based on PP. No.10 / 1990 (updated to PP.No.103 / 2000) transformed again into a Public Company (PERUM). Then based on PP No. 51/2011 dated December 13, 2011 legal form Pawnshop changed again into a Limited Liability Company (PERSERO). A step change in status Pawnshop be Limited is part of the effort to reorganize or restructure the SOEs as planned in the master plan SOE 2010-2014. With legal status in the form of limited liability company is a pawnshop expected to be better able to manage their business more professional, market mechanism without leaving his trademark, namely: lending on the basis of the law of pledge to target rural communities in social and economic status were weak due to the system of economy very liberal, to the pawnshop must improve the efficiency and effectiveness of services to the public or customers. Given the ministry in the service of this credit is still trusted by the public medium is Pawnshop, amid the economic situation the country is still experiencing instability as a result of the situation and the impact of global economic upheaval